2015
DOI: 10.3390/soc5040686
|View full text |Cite
|
Sign up to set email alerts
|

A Call to Action: Developing and Strengthening New Strategies to Promote Adolescent Sexual Health

Abstract: Through considerable efforts and investments of resources, adolescent pregnancy and birth rates in the United States have decreased significantly over the past two decades. Nonetheless, large disparities persist for many populations of youth. Reducing unintended adolescent pregnancies is considered a "winnable public health battle," but one that will require innovative thinking and continued persistence. This paper reviews the recent research literature and innovative programmatic efforts to identify six promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 117 publications
(143 reference statements)
0
10
0
1
Order By: Relevance
“…One study conducted with lesbian, gay, and bisexual students found that those in schools with inclusive sexual health education reported fewer sexual partners, less recent sex, and less substance use before having sex than those in schools that did not provide inclusive sexual health education (Blake et al, 2001). Literature on how to make sexual health education more relevant for sexual minority youth is sparse but growing, and it calls for discussions of sexual orientation as a way to keep these youth, who may be at a greater risk of adverse sexual health outcomes, engaged in sexual health education (Blake et al, 2001; CDC, 2012; Cohen et al, 2004; Decker, Berglas, & Brindis, 2015; Fisher et al, 2009; Gowen & Winges-Yanez, 2014). Recent calls-to-action have further described inclusive sexual health education (Advocates for Youth, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted with lesbian, gay, and bisexual students found that those in schools with inclusive sexual health education reported fewer sexual partners, less recent sex, and less substance use before having sex than those in schools that did not provide inclusive sexual health education (Blake et al, 2001). Literature on how to make sexual health education more relevant for sexual minority youth is sparse but growing, and it calls for discussions of sexual orientation as a way to keep these youth, who may be at a greater risk of adverse sexual health outcomes, engaged in sexual health education (Blake et al, 2001; CDC, 2012; Cohen et al, 2004; Decker, Berglas, & Brindis, 2015; Fisher et al, 2009; Gowen & Winges-Yanez, 2014). Recent calls-to-action have further described inclusive sexual health education (Advocates for Youth, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the rates of STIs are increasing among adolescents and disproportionately affect youth from certain racial, ethnic, geographic, and socioeconomic backgrounds [ 20 ]. Too often, sexual health education and services do not reach these youth or do not reflect their experiences and backgrounds [ 21 ]. In many cases, youth who are at the greatest need for comprehensive programming are less likely to receive it.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, youth who are at the greatest need for comprehensive programming are less likely to receive it. For example, youth who frequently move, are unstably housed, or in foster care may miss school-based programming [ 21 , 22 ]. Similarly, few sex education curricula are designed to be inclusive of same-sex partners, sexual orientation, or gender identity [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teenage pregnancy leads to a high rate of maternal mortality, infant mortality, and various risks for babies. Therefore, strategies to prevent teen pregnancy, which include enhancing knowledge and building positive attitudes as well as personal development, are of prime importance [6]. These pregnancy prevention strategies were proven effective in reducing the risk of teenage pregnancy, as some individual states in the United States, for example, saw a successful reduction of 82% in the number of adolescent pregnancy [7].…”
Section: Introductionmentioning
confidence: 99%